2021
DOI: 10.13075/mp.5893.01207
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic application of mesenchymal stem cells in COVID-19 complications

Abstract: Mesenchymal stem cells (MSCs) have remarkable immunomodulatory properties, low immunogenicity, and paracrine properties as well as the ability to differentiate into multiple cell lines. These properties make them potential candidates for clinical applications in the treatment of neurodegenerative, cardiovascular, and lung diseases, which may be occupational diseases. Preclinical studies using experimental animal models have demonstrated regenerative properties of MSCs in diseases such as silicosis and occupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…One week later, the expression of CD73 and STEM121 in the testis tissue of the control group (PBS + hUC-MSCs) and PTX + hUC-MSCs treatment group could still be detected. The results suggested that hUC-MSCs can survive for a long time in mouse testis tissue and exert effective paracrine immunomodulatory function to repair tissue damage [ 22 24 ]. After 2 weeks, significant changes in testicular morphology and key proteins related to spermatogenesis were identified in PTX-treated mice testis, and the application of hUC-MSCs (2 × 10 6 cells) significantly improved these changes and elevated antioxidant levels.…”
Section: Discussionmentioning
confidence: 99%
“…One week later, the expression of CD73 and STEM121 in the testis tissue of the control group (PBS + hUC-MSCs) and PTX + hUC-MSCs treatment group could still be detected. The results suggested that hUC-MSCs can survive for a long time in mouse testis tissue and exert effective paracrine immunomodulatory function to repair tissue damage [ 22 24 ]. After 2 weeks, significant changes in testicular morphology and key proteins related to spermatogenesis were identified in PTX-treated mice testis, and the application of hUC-MSCs (2 × 10 6 cells) significantly improved these changes and elevated antioxidant levels.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, MSC TXs have the potential to improve the management of the new illness COVID-19. 49 MSCs are non-hematopoietic cells (n-HPC) with a strong proliferative capacity and multi-lineage differentiation abilities. 50,51 MSCs have been employed for almost 3 decades and have demonstrated tremendous advances.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…MSCs might be a viable therapeutic or supplemental agent for COVID-19 therapy. 49 They are widely used because of factors such as their low immunogenicity. MSCs are not identified by the human Immune System (IS) due to poor expression of Major Histocompatibility Complex (MHC) particles and an undetectable level of MHC-II.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…To address this problem, effective tests must be put in place for the rapid recognition of bacterial or viral diseases [ 13 ]. In this field, microbiological research needs to be expanded for adjuvant therapy with bacterial strains that are beneficial to the human microbiota, and which use probiotics and stem cells during viral infection [ 32 , 33 , 34 , 35 , 36 ]. Moreover, because the aspiration of oral bacteria induces the expression of angiotensin-converting enzyme 2, a receptor for SARS-CoV-2, and production of inflammatory cytokines in the lower respiratory tract, poor oral hygiene can lead to COVID-19 aggravation [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Microbiological Perspectives In Pandemicsmentioning
confidence: 99%